Effects of organic cations on optical properties and structural stability in two-dimensional hybrid perovskites - Lekina, Yulia (Nanyang Technological University, 2021)
Two-dimensional (2D) hybrid organic-inorganic lead halide perovskites have been extensively studied in the last few years. Tunability and improved stability over their 3D counterparts make them promising materials for applications in various technologically important areas. Extended chemical engineering possibilities allow control of the functional properties, such as band gap, light emission, conductivity or spin-related effects. 2D perovskites, consisting of alternate semiconducting inorganic lead halide and insulating organic layers, form natural multiple quantum well structures, where the optoelectronic properties are primarily determined by the inorganic sublattice, and the tunability can be directly achieved by varying the composition, thickness and structure of the lead halide layers. However, the organic layers also influence the material properties as well, for example affecting the crystal structure by sterical factors, as well as through direct interactions with the inorganic sublattice. In this thesis, we investigate how the properties of 2D perovskites are dependent on the nature of the organic cations by utilizing optical and vibrational spectroscopy in a wide temperature and pressure range. Our work reveals that various modifications of the organic groups cause some specific changes in the perovskites. For example, combining small methylammonium MA+ and bulky phenylethylammonium PEA+ organic cations results in the multidimensional perovskite (PEA)2(MA)[Pb2I7] that is significantly more stable in comparison with the 3D (three-dimensional) counterpart. On the other hand, the small MA+ cation has rotational degree of freedom, that is not typical for the long interlayer chains. The state of the small cation is shown to influence the optical properties of the multidimensional perovskites. When a 2D perovskite with corrugated inorganic layers is formed with a relatively short asymmetric imidazolium-ethylammonium bication, strong in-plane anisotropy of the optoelectronic properties and exciton-phonon coupling were observed. The compressibility and high-pressure evolution in 2D perovskites with naturally anisotropic mechanical properties are of particular interest. Unlike other materials, PL intensity in some perovskites increase markedly under pressure. Besides, the perovskites are known to show a series of phase transitions, which involve the Pb-I bond length and angle changes and impact the energy band gap. In 2D perovskites, the choice of the interlayer organic cation affects the phase transitions variety and structural stability. Therefore, relatively strong π- π interactions between benzene rings result in more stable and rigid perovskites. In contrast, choosing the long flexible hexadecylammonium organic cation resulted in a rich variety of responses of the material to high pressure. The thick and soft organic layer is shown to be more compressible and exhibit more degrees of freedom in response to pressure, resulting in the disordering of the organic sublattice, which in turn influence the structure of the inorganic octahedra and hence the electronic structure and optical properties. In summary, we systematically investigated how the choice of the organic cations in 2D perovskites affects their structural and optical properties, which often results in special and exclusive features. Our work contributes to the understanding of fundamental optical and physical properties of two-dimensional perovskites.